Rainbow Trout IgM+ B Cells Preferentially Respond to Thymus-Independent Antigens but Are Activated by CD40L - Granja, Aitor G.; Perdiguero, Pedro; Martín-Martín, Alba; Díaz-Rosales, Patricia; Soleto, Irene; Tafalla, Carolina (Frontiers in Immunology, 2019)
In the absence of class switch recombination (CSR) and germinal centers (GCs), the mechanisms through which B cells from teleost fish mount extrafollicular IgM memory responses remains mostly unexplored. In this report, we demonstrate that teleost IgM+ B cells respond to CD40L, a thymus-dependent (TD) activation signal, similarly to mammalian B2 cells. However, when stimulated with different types of antigens, fish IgM+ B cells only reach a general activation state in response to antigens catalogued as thymus-independent 1 (TI-1) in mammals, as established through both functional assays and RNA sequencing. Interestingly, fish IgM+ B cells remained completely unresponsive to TI-2 antigens, suggesting that the engagement of innate receptors provided by TI-1 antigens is required for the activation of teleost B cells. Finally, a synergy between CD40L and TI-1 antigens was also demonstrated, further supporting that there is no clear dichotomy between TD and TI responses in teleost fish.